Markt und Marktwirtschaft - Roland Kirstein (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2006)
Der Beitrag führt in das Konzept der Marktwirtschaft ein. Im Vergleich mit anderen Wirtschaftsordnungen wird der Preismechanismus als entscheidender Unterschied herausgestellt, der zugleich Anreiz- und Informationswirkung entfaltet und somit Ineffizienzprobleme der alternativen Systeme zu überwinden vermag. Die strengen Anforderungen der ökonomischen Theorie müssen nicht einmal erfüllt sein, wie Experimente gezeigt haben. Allerdings kann es aufgrund externer Effekte, asymmetrischer Information oder natürlicher Monopole zu Marktversagen kommen; ein weiterer Ansatzpunkt für die Notwendigkeit staatlicher Regulierung wären unerwünschte Verteilungswirkungen. Der Beitrag nimmt Bezug auf die moderne Institutionenökonomik und geht auf makroökonomische Erwägungen ein. – – The paper provides an introduction to market economy. In comparison to other economic systems, the most important difference appears to be the existence of market prices which are created spontaneously. Hence, prices do not only provide an incentive system, but also aggregate dispersed information. Experiments have demonstrated that the price system may render efficiency even if the strict assumptions of economic theory are not fulfilled. However, inefficiency can arise due to market failure. A further justification for governmental regulation of markets can be found in unsatisfying distributional results. The paper briefly highlights the relations of neoclassical theory with modern institutional economics as well as with macroeconomics.
Keywords: P10; B20; A10; 330; market failure; spontaneous order; Ordoliberalism; experiments; efficiency